Silver in Iceland: A History - Ann Elizabeth Bailey 1994- (2018)
When one thinks of the Viking Age various thoughts come to mind, from horned helmets (thanks to Hollywood), bearded burly men, long boats, and, most importantly, silver. Silver is undoubtedly a significant part of the Icelandic settlement from archaeological finds to the sagas. The aim of this thesis is to create a comprehensive history and timeline of silver in Iceland up until the decline of the Viking Voyages around the beginning of the twelfth century. While not an exhaustive catalog of all current silver finds, I hope to address key components to create a full image of silver history in Iceland. The silver itself reflects the Viking Age in the Nordic countries as expected, without any major outliers. The quantity however, is much less than in Iceland´s Norse counterparts.